GIS-based strategic approach for land suitability analysis to beekeeping of Apis cerana and A. mellifera in China (Plant Bulletin, 2025)
The importance of honeybees in honey production and environmental services is undeniable. Beekeeping plays a vital role in supporting these services. To improve honeybee performance and address the declining populations of Apis cerana and A. mellifera, it is essential to conduct land suitability analyses for beekeeping in China, the world’s largest beekeeping country. Our strategic fuzzy logic approach integrated within a GIS (Geographical Information Systems) framework provides guidance on reducing colony loss risks and ultimately enhancing honey production by identifying the most suitable lands for beekeepers. In this study, the most influential environmental and ecological factors affecting beekeeping were incorporated to develop land suitability maps. Our approach revealed that 37% and 32% of China’s land area is highly suitable for A. cerana and A. mellifera, respectively. Approximately 24% of the area was found to be commonly suitable for both species. Most of the highly suitable areas for A. mellifera were concentrated in specific parts of southern, central, and eastern China. In contrast, A. cerana suitability was widespread across China, excluding the Tibetan Plateau. The reliability of this approach was further confirmed through validation using actual beekeeping locality data. Overall, our findings indicate that while apicultural practices can be expanded across a large portion of China, the most favorable conditions are limited to specific regions. Identifying these optimal zones can help enhance colony productivity and reduce the risk of colony losses.